Learning Islamic Religious Education by Utilizing Online Media in Junior High Schools - Muhammad Auva Romadhon; Syaad Patmanthara; Moh. Afifullah (Journal of Science and Education (JSE), 2024)
This study aims to analyze the planning, implementation, and evaluation models of the use of online-based learning media in Islamic Religious Education (PAI) learning at SMP Sunan Kalijogo Jabung. This type of research is qualitative with a phenomenological approach. Data collection uses observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions/verification. The results of the study show that in planning, PAI teachers pay attention to student conditions, facilities and infrastructure, and the school environment before compiling objectives, teaching materials, methods, media, and evaluation techniques. The application of online media involves the use of learning videos from YouTube which are analyzed by students and reinforced with direct explanations. Teachers also involve students in creating learning video content to be uploaded to YouTube. Evaluation is carried out through the Project-Based Learning (PjBL) approach by assessing the creativity, activeness, and suitability of learning videos made by students to the material being taught